The Influence of Organizational Structure, Leadership and Human Resource Capability on Service Effectiveness - Rahmad, Rahmad; Sabri, Sabri; Nasfi, Nasfi (IJOSMAS, 2021)
The purpose of this study is to reveal the effect of organizational structure (X1) on the effectiveness of land rights certification services (Y) at the Land Office of West Pasaman Regency, to determine the influence of leadership (X2) on the effectiveness of land rights certification services (Y) at the Pasaman Regency Land Office. West, to determine the effect of the ability of Human Resources (X3) on the effectiveness of land rights certification services (Y) at the Land Office of West Pasaman Regency and to jointly determine the effect of organizational structure, leadership and human resource capabilities on the effectiveness of rights certification services. on land at the West Pasaman Regency Land Office. The research respondents were 35 employees of the Land Office of West Pasaman Regency who did not have a structural position (not as an element of leadership), the data was taken by the census method, meaning the number of respondents in the population was the same as the sample. The analytical tool used is Multiple Linear Regression using the SPSS (Statistical Package For Social Science) program. The findings of this study; 1) there is an influence between organizational structure and service effectiveness, there is a significant influence between organizational structure and service effectiveness at the West Pasaman Regency Land office, 2) there is a significant influence between leadership and service effectiveness at the West Pasaman Regency Land Office, 3) There is an influence between the ability of Human Resources and the effectiveness of services and there is a significant influence between the ability of Human Resources and the effectiveness of services at the Land Office of Pasaman Barat Regency, and 4) there is a joint influence of the organizational structure, leadership and capabilities of Human Resources on the effectiveness of services at the Land Office of West Pasaman Regency.